Designing for Networked Learning in 360VR - A scenographic turn in online learning environments? - Davidsen, Jacob Gorm; Vinter Larsen, Dorthe; Paulsen, Lucas; McIlvenny, Paul (Proceedings of the International Conference on Networked Learning, 2024)
Despite the growing popularity of Virtual Reality (VR) in Higher Education (HE), there is a lack of studies dealing with networked and collaborative activities in VR (Radianti et al., 2020). Historically, VR has been promoted as an educational technology that can give access to exotic places or dangerous situations through computer-generated virtual worlds. Another area of application of VR has been therapeutical sessions exposing individuals to unknown situations. Concepts like interactivity, immersion and presence has been shaping the discourse of educational VR (Markowitz & Bailenson, 2019), but that is not necessarily supporting a networked or collaborative learning approach. Recently, 360-degree video cameras has made it possible to record situated practices, which can then be used as the canvas in the virtual world (McIlvenny & Davidsen, 2017). Pirker et al. (2021) argued that 360VR could potentially be a game-changer for distant education, but it is also clear that 360VR pose a new medium for supporting Networked Learning. Basically, 360VR presents a transition from logocentric platforms (e.g. Moodle) emphasising the exchange of text between peers towards platforms that build upon ideas of immersion, inhabitation and multimodality. The aim of the workshop is to discuss how principles of Networked Learning can inform the design of 360VR activities in HE. CAVA360VR is a prototype Unity-based Windows application supporting 20 simultaneous participants to collaboratively analyse, visualise and annotate 360° video in VR. CAVA360VR is developed by the BigSoftVideo team (www.bigvideo.aau.dk) in Aalborg University (McIlvenny, 2020). In CAVA360VR, remote participants can share, view and interact with a 360° video together, draw on the 360° video, use a ‘mirror-cam’ to see what is behind you, use a laser pointer to guide others’ attention, import a 2D image, view a transcript, and view a synced 2D video with the 360° video. Further, participants can talk to each other, and the audio is spatialized in the VR environment. In CAVA360VR, each participant is represented with an avatar that follows the orientation of the Head Mounted Display (HMD) of the individual participant and the controllers are showed as pair of avatar hands. The potential of CAVA360VR is also particularly interesting in the context of Networked Learning as it offers a new platform for designing for learning. CAVA360VR is not only available in VR, but can also run as a standard desktop application, which allows a larger, mixed group to participate in the analysis of the recorded data. Not all of the features available in VR are available in non-VR mode. For two years, CAVA360VR has been used in many video data sessions (Jordan & Henderson, 1995; McIlvenny, 2020) with participants – for example, from Ghana, Finland and Denmark – analysing 360° video data together. The potential of CAVA360VR is also particularly interesting in the context of Networked Learning as it offers a new platform for designing for learning. This includes addressing how to collect 360 video data, how to pedagogically design activities, and how to support students negotiating of meaning in 360VR, etc.